Long Non-Coding RNA LINC01410 Promoted Tumor Progression via the ErbB Signaling Pathway by Targeting STAT5 in Gallbladder Cancer - Lu, Lili; Zhang, Shilong; Song, Zhengqing; Lu, Weiqi; Wang, Zhiming; Zhou, Yuhong (Frontiers in Oncology, 2021)
Objectives: Long noncoding RNAs (lncRNAs) have been recently emerging as crucial molecules in multiple human cancers. However, their expression patterns, roles as well as the underlying mechanisms in gallbladder cancer (GBC) remain largely unclear. Materials and Methods: The expression patterns of lncRNAs in GBC were downloaded from GEO database. Quantitative real-time polymerase chain reaction (qRT-PCR) and RNA in situ hybridization (ISH) were used to detect the expression levels of lncRNAs in GBC patient samples. The full-sequence of LINC01410 was determined by RACE assay. Subcellular distribution of LINC01410 was examined by nuclear/cytoplasmic RNA fractionation analysis. Loss- and gain- of-function experiments were conducted to explore the biological functions of LINC01410 in vitro and in vivo. RNA pull-down, RNA immune-precipitation (RIP), and Western blot assay were conducted to investigate the mechanisms underlying the biological function of LINC01410 in GBC. Results: LINC01410 was significantly up-regulated in GBC tissues compared to the adjacent non-tumor tissues. High LINC01410 expression was significantly associated with lymphatic metastasis and poor prognosis of GBC patients. We identified LINC01410 to be 2877 bp in length and mainly localized in the cytoplasm of GBC cells. Overexpression of LINC01410 promoted GBC cells proliferation, migration, and invasion in vitro and GBC progression in vivo, whereas LINC01410 down-regulation rescued these effects in vitro. From RNA pull-down and RIP assay, we identified that STAT5 was a critical downstream target of LINC01410. Furthermore, ErbB signaling pathway was involved in the LINC01410 regulated the malignant phenotypes of GBC. Conclusions: LINC01410 is an important lncRNA that promotes GBC progression via targeting STAT5 and activating ErbB signaling pathway. Thus, LINC01410 may be a promising diagnostic and therapeutic target for GBC patients.